1999
DOI: 10.1128/aem.65.2.626-631.1999
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compressed Carbon Dioxide on Microbial Cell Viability

Abstract: In order to study the influence of compressed carbon dioxide, over a range of pressures (1.5 to 5.5 MPa) and exposure times (up to 7 h), on the survival of Escherichia coli,Saccharomyces cerevisiae, and Enterococcus faecalis, a new pressurizable reactor system was conceived. Microbial cells were inoculated onto a solid hydrophilic medium and treated at room temperature; their sensitivities to inactivation varied greatly. The CO2 treatment had an enhanced efficiency in cell destruction when the pressure and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(49 citation statements)
references
References 18 publications
(35 reference statements)
2
45
1
1
Order By: Relevance
“…Despite the industrial relevance of CO 2 effects on yeast physiology, little is known or understood about the molecular mechanisms involved in CO 2 sensitivity in S. cerevisiae. Proposed mechanisms for CO 2 include alterations in membrane fluidity (the so-called ''anaesthesia effect''), direct inhibition of certain enzyme activities and internal acidification by the hydration of CO 2 into H 2 CO 3 , but all of these are essentially hypothetical [1].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the industrial relevance of CO 2 effects on yeast physiology, little is known or understood about the molecular mechanisms involved in CO 2 sensitivity in S. cerevisiae. Proposed mechanisms for CO 2 include alterations in membrane fluidity (the so-called ''anaesthesia effect''), direct inhibition of certain enzyme activities and internal acidification by the hydration of CO 2 into H 2 CO 3 , but all of these are essentially hypothetical [1].…”
Section: Introductionmentioning
confidence: 99%
“…Difference in substrates may also contribute to differences in processing times. Previously, a CO 2 sterilization process was proven effective before for both S. aureus (Dillow et al, 1999;Kamihira et al, 1987) and E. coli (Ballestra et al, 1996;Debs-Louka et al, 1999;Dillow et al, 1999;Erkmen, 2001a;Isenschmid et al, 1992;Kamihira et al, 1987;Schmidt et al, 2005) suspended in a liquid solution, in slurry form and when inoculated onto a solid hydrophilic medium but sterilization has not been investigated with the bacteria embedded in a polymeric matrix. Kamihira et al (1987) accomplished killing of E. coli in culture media (6-log reduction) and S. aureus (5 log-reduction) by treating with SC-CO 2 at similar experimental conditions (20.6 MPa and 358C) (Kamihira et al, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…As determined in other studies, the mechanism of inactivation was due to dissolving carbon dioxide in aqueous phase, then carbonic acid was formed and decreased the pH, which reduced the microorganism resistance to heat. Subsequently, CO 2 diffused into the cells and inactivated the bacteria by extraction of vital compounds, modifying the enzymatic activity and denaturation (Debs-Louka et al, 1999;Garner et al, 2006). These effects were enhanced by addition of water, ethanol, and hydrogen peroxide.…”
Section: Effect Of Additives On Co 2 Inactivation Efficiencymentioning
confidence: 99%
“…The sterilization process was not completely effective for the inactivation of all mircroorganisms, and therefore the pressure was altered. Garner et al (2006), Debs-Louka et al (1999), and Zhang et al (2006b) found that increasing the pressure improved the CO 2 sterilization efficiency for different types of bacteria, presumably due to enhancing the dissolution of vital compounds and further decrease in pH. The lipids in the cell membrane may be dissolved by carbon dioxide at higher pressures, which increases cellular penetration and hence microbial inactivation.…”
Section: Effect Of Temperaturementioning
confidence: 99%
See 1 more Smart Citation